ПРОЦЕС ІНТЕЛЕКТОКОРИСТУВАННЯ ЯК ФУНДАМЕНТАЛЬНА ПРОБЛЕМА РАЦІОНАЛІЗАЦІЇ ВИКОРИСТАННЯ ЛЮДСТВОМ ПРИРОДНИХ РЕСУРСІВ ПЛАНЕТИ - Петренко, В. П.; Кісь, С. Я.; Каламбет, Я. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
1